2008
DOI: 10.1021/np070647y
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes from Celastrus vulcanicola as Photosynthetic Inhibitors

Abstract: Three new sesquiterpenoids (1- 3) with a dihydro-beta-agarofuran skeleton were isolated from Celastrus vulcanicola. Their structures were elucidated on the basis of spectroscopic analysis, including homonuclear and heteronuclear correlation NMR experiments (COSY, ROESY, HSQC, and HMBC), and the absolute configurations were determined by circular dichroism and chemical correlations. Their effects on photosynthesis were tested. Sesquiterpene 1 (50 microM) inhibits both light-dependent synthesis of ATP and the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 24 publications
3
39
0
1
Order By: Relevance
“…As indicated in Table , there are a number of known NPs that inhibit photosynthesis by blocking electron flow at the quinone binding site of D‐1 protein on the reducing side of photosystem II (PSII) . Most of these have a structural resemblance to plastoquinone in having both a cyclic dione substructure and an aliphatic side chain.…”
Section: Herbicidesmentioning
confidence: 99%
“…As indicated in Table , there are a number of known NPs that inhibit photosynthesis by blocking electron flow at the quinone binding site of D‐1 protein on the reducing side of photosystem II (PSII) . Most of these have a structural resemblance to plastoquinone in having both a cyclic dione substructure and an aliphatic side chain.…”
Section: Herbicidesmentioning
confidence: 99%
“…In the present work, and as a continuation of our research on Celastrus vulcanicola (Torres-Romero et al, 2008, 2009 and Maytenus jelskii (Perestelo et al, 2011), we report herein on the isolation and structural elucidation of nine new friedelane-type triterpenes (1-9), along with twenty two known ones (10-31) (Fig. 1).…”
Section: Introductionmentioning
confidence: 81%
“…Further investigations showed that (14) has two targets of interaction: one is located at the oxygenevolving complex, and the other located at the H + -ATPase complex. Compound (15) behaves likewise to (14) albeit being less active (Torres-Romero et al, 2008). The fractioning of the hexane extract from air-dried leaves of Maytenus imbricata led to the isolation of seco-3,4-triterpenoid (16).…”
Section: Natural Products As Source Of Photosynthetic Inhibitorsmentioning
confidence: 98%
“…The survey of literature revealed that various other terpenes ( Figure 5) have been evaluated as potential inhibitors of photosynthesis in a similar manner described for compounds (12) and (13). The sesquiterpenoids (14) and (15) were isolated from the dichoromethane extract of the leaves of Celastrus vulcanicola (Torres-Romero et al, 2008). Similar to what happens to other terpenes, both compounds are capable of inhibiting the photosynthetic photophosphorylation in isolated spinach chloroplasts from water to methylviologen in a concentration-dependent manner (IC 50 = 25 mol L -1 for 14 and IC 50 = 44 mol L -1 for 15).…”
Section: Natural Products As Source Of Photosynthetic Inhibitorsmentioning
confidence: 98%